2008
DOI: 10.1071/fp08113
|View full text |Cite
|
Sign up to set email alerts
|

Transient shade and drought have divergent impacts on the temperature sensitivity of dark respiration in leaves of Geum urbanum

Abstract: The respiratory response of plants to temperature is a critical biotic feedback in the study of global climate change. Few studies, however, have investigated the effects of environmental stresses on the short-term temperature response of dark respiration (Rdark) at the leaf level. We investigated the effect of shade and transient drought on the temperature sensitivity (Q10; the proportional increase in respiration per 10°C increase in temperature) of Rdark of Geum urbanum L. in controlled experiments. Shade e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 75 publications
3
44
1
Order By: Relevance
“…The effects of drought stress on plant respiration vary according to the severity of the stress and also among species [52]. The increase in respiration observed in WT plants could reflect a strategy by the plant to increase ATP levels to repair the damage caused by drought and salt stress, as demonstrated by Slot et al [53] in drought-stressed Geum urbanum leaves. Considering that AtUCP1 overexpression reduced the deleterious effects of abiotic stress, the need for higher respiration rates was reduced, leading to higher biomass accumulation, which might also be enhanced by the higher photosynthesis under stress.…”
Section: Discussionmentioning
confidence: 85%
“…The effects of drought stress on plant respiration vary according to the severity of the stress and also among species [52]. The increase in respiration observed in WT plants could reflect a strategy by the plant to increase ATP levels to repair the damage caused by drought and salt stress, as demonstrated by Slot et al [53] in drought-stressed Geum urbanum leaves. Considering that AtUCP1 overexpression reduced the deleterious effects of abiotic stress, the need for higher respiration rates was reduced, leading to higher biomass accumulation, which might also be enhanced by the higher photosynthesis under stress.…”
Section: Discussionmentioning
confidence: 85%
“…This result may reflect a longer-term response to prolonged drought stress that increased the demand for maintenance respiration, as has been seen in other studies (Gratani et al . 2007; Slot et al . 2008; Atkin and Macherel 2009).…”
Section: Discussionmentioning
confidence: 99%
“…2006), but drought may also increase respiration as result of increased respiratory demand for ATP (Atkin and Macherel 2009) or increased maintenance respiration (Gratani et al . 2007; Slot et al . 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Plant photosynthesis and respiration (R) are interdependent processes but are both dependent on leaf temperature. However, both processes respond differently and non‐linearly to environmental temperature (Slot et al ), with respiration being more sensitive to temperature (Amthor ), which may have a significant impact on plant carbon gain (Turnbull et al ). Turnbull et al () reported that nocturnal temperatures have a significant effect on the photosynthetic capacity of leaves during the subsequent day, through its impact on leaf respiration and carbohydrate status.…”
Section: Introductionmentioning
confidence: 99%